Le droit de l'emploi au Québec - Trudeau, Gilles (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "Le droit de l'emploi au Québec," by Fernand Morin and Jean-Yves Brière.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z